2012
DOI: 10.1111/j.1365-2672.2012.05331.x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of ochratoxin A and zearalenone by potential probiotic Saccharomyces cerevisiae strains and its relation with cell wall thickness

Abstract: Aims:  To examine Saccharomyces cerevisae strains with previously reported beneficial properties and aflatoxin B1 binding capacity, for their ability to remove ochratoxin A (OTA) and zearalenone (ZEA) and to study the relation between cell wall thickness and detoxificant ability of yeast strains. Methods and Results:  A mycotoxin binding assay at different toxin concentrations and the effect of gastrointestinal conditions on mycotoxin binding were evaluated. Ultrastructural studies of yeast cells were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…Armando et al . () were showed that Saccharomyces cerevisiae RC012 and RC016 strains in vitro conditions had the highest OTA adsorption percentages and the cell diameter/cell wall thickness relation revealed a correlation between cell wall amount and mycotoxin elimination stability. A yeast‐based product was reported to adsorb up to 68% ZEA, 29% AFB 1 and 62% OTA (Joannis‐Cassan et al .…”
Section: Discussionmentioning
confidence: 93%
“…Armando et al . () were showed that Saccharomyces cerevisiae RC012 and RC016 strains in vitro conditions had the highest OTA adsorption percentages and the cell diameter/cell wall thickness relation revealed a correlation between cell wall amount and mycotoxin elimination stability. A yeast‐based product was reported to adsorb up to 68% ZEA, 29% AFB 1 and 62% OTA (Joannis‐Cassan et al .…”
Section: Discussionmentioning
confidence: 93%
“…The union of binder probiotics with toxins reduces their availability and, consequently, the absorption of the toxin in the gastrointestinal tract. Reduction in other major mycotoxins, aflatoxin B 1 , zearalenone and ochratoxin A, by the probiotic S. cerevisiae RC016 strain has also been shown in vitro (Armando et al , 2012. In the absence of a simple detoxification method for foods and feeds contaminated by FB 1 , the use of yeast selected strains appears as a promising approach to reduce their toxicological effects.…”
Section: Discussionmentioning
confidence: 99%
“…for aflatoxin bound by lactobacilli, and enterobacteria (Fazeli et al, 2009;Serrano-Niño et al, 2013) or for OTA bound by wine lactic acid bacteria (Del Prete et al, 2007). Concerning the strong effect of the kind of the strain, some possible ideas could be: (i) the total charge and its distribution, the size of the pores and the surface area (Huwig, Freimund, Kappeli, & Dutler, 2001), but also (ii) dissimilar cell diameter⁄ cell wall thickness relation (Armando et al, 2012) or (iii) differences in the composition of cell wall: e.g. a high chitin content decreased the flexibility of cell wall with a consequent lower capacity to form complexes with zearalenone in S. cerevisiae (Yiannikouris et al, 2004).…”
Section: Strainsmentioning
confidence: 99%